Existential Trauma in Times of CoVIEd and the Beirut Blast (Existential Analysis: Journal of the Society for Existential Analysis, 2021)
This paper proposes several linked terms that I hope will contribute to our explorations of the lived experiences of our clients living through the CoVIEd context, and the Blast of Beirut, just two very different potentially traumatising events of the past few months. It takes the form of a creative meander across troubled terrain. With a mix of terms from social anthropology, the paper introduces new perspectives on these times of collective existential trauma in which the triple relating of self, others and the world are impacted. The paper considers the relationship between fear of pollution, increased polarisation and social disorder.
Keywords: Existential trauma; triple relating; creative reflecting; creative anxiety; COVID communitas; symbolic glue; unconclusive liminality; creative plasticity; phenomenal creativity